Quantifying the functional responses of vegetation to drought and oxygen stress in temperate ecosystems - Douma, Jacob C.; Bardin, Vincent; Bartholomeus, Ruud P.; van Bodegom, Peter M. (Functional ecology, 2012)
1. Our understanding of the generality of plant functional responses to water availability is limited; current field studies use either very rough approximations of water and oxygen availability or only focus on water-stressed ecosystems. Studies that relate species' responses to a surplus of water are limited to controlled experiments. 2. The aim of this study was to investigate how traits are selected along a gradient of soil moisture, ranging from oxygen-stressed to drought-stressed. We tested 15 traits: eight leaf traits, two root traits, two seed traits and three allometry traits and related their community means to process-based measures of drought stress and oxygen stress for 171 plots in the Netherlands. Because the trait values had been taken from a large database, an independent field survey was carried out to validate the relationships thus derived. 3. We show that root porosity and seed floating capacity are mostly strongly related, although still moderately, to oxygen and drought stress (R 2 = 27% and 42%, respectively). Leaf traits responded weakly to either of the stressors. The field survey yielded similar relationships. Trait combinations were much more closely related to oxygen or drought stress than individual traits, suggesting that there are multiple trait solutions at a given level of water and oxygen stress. 4. The relatively weak relationships found between traits and water-related stressors contrast with the strong control of other environmental drivers (disturbance, nutrients) on traits and suggest that these strong constraints imposed by other environmental drivers necessitate varied solutions to cope with water availability.